Old age in the Brazilian business press: new cultural sensibilities in a financialized economy - Soulé, Fernanda Veríssimo (Organizações & Sociedade, 2019)
The financialization of the economy has been extensively studied in economic and organizational sociology. This literature focuses on changes in organizations associated to the shareholder value culture and on how financialization influences several domains of life. Based on the literature from this broad scope of social impacts of financialization and on sociological approaches to old age, this paper analyzes the predominant conceptions of old age diffused by the Brazilian business press in the context of increasing longevity of the population and their relation with the emergence of the financialized economy in Brazil. To address the issue, we carried out a content analysis of the 636 issues of Exame, the main Brazilian business magazine, comprising the period from 1990 to 2014. A corpus of 230 articles was then selected and systematically assessed. The results were analyzed combining ideas from the Reflexive Sociology of Bourdieu and the Pragmatic Sociology of Boltanski. Four ideas or aspects prevailed in the material assessed: i.) planning for retirement; ii.) rationalized life and financial approach to old age; iii.) population aging and its micro and macroeconomic impacts, and; iv.) generational demarcation and disputes in organizations. Economic logic was dominant, reflecting in more or less explicit proposals of a financial model to frame life.